Perovskite passivation material, passivation layer and cell thereof
By using the zwitterionic polymer compound formula A on the surface of the absorption layer of the perovskite solar cell, the problems of poor stability and low photoelectric conversion efficiency of perovskite solar cells in high temperature and high humidity environments are solved, and more efficient photoelectric conversion and long-term performance maintenance are achieved.
Patent Information
- Application Number
- CN202510060400.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2045-01-15
AI Technical Summary
The existing perovskite solar cells have poor stability and low photoelectric conversion efficiency in high temperature and high humidity environments, and the existing passivation layer materials cannot effectively suppress interface charge recombination, affecting the long-term performance of the battery.
The zwitterionic polymer compound formula A is used as the passivation layer material for the perovskite absorption layer. The passivation layer is prepared by introducing the compound of formula A on the perovskite surface to increase the perovskite grain radius and improve the interfacial charge recombination problem.
Effectively inhibit the interfacial charge recombination between perovskite and electron transport layer, improve the photoelectric conversion efficiency and stability of perovskite photovoltaic devices, maintain the long-term performance of the battery, and simplify the preparation process of passivation layer, and reduce costs.
Smart Images

Figure CN119859116A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of perovskite solar cells, and in particular to a perovskite passivation material, a passivation layer and a cell thereof. Background Art
[0002] Since perovskite solar cells first achieved a photoelectric conversion efficiency of 3.8% in 2009, perovskite materials have become a hot semiconductor material, with the highest photoelectric efficiency exceeding that of silicon cells, reaching 26.7%. However, the poor stability and short life of perovskite solar cells have always restricted their commercial development.
[0003] In the traditional method of preparing perovskite films, the perovskite films prepared by the solution method usually contain a large number of grain boundary defects, which cause water and oxygen in the air to penetrate into the perovskite through these defects, thereby causing the perovskite to decompose. At the same time, due to the unstable energy of interface defects, it is easily destroyed by external factors (such as light, electric field, heat, etc.), which will also accelerate the decomposition of perovskite. In order to improve the stability problem, various strategies for perovskite defect passivation and inhibition of ion migration have been developed to date, such as perovskite component engineering, anti-solvent engineering, and additive engineering. However, under high humidity and high humidity conditions, unencapsulated perovskite solar cells still have low stability and low photoelectric conversion efficiency. Therefore, how to design a perovskite solar cell with good tolerance to high temperature and high humidity has become a problem that needs to be solved urgently.
[0004] Although the existing technology has solved the problems of perovskite solar cells to a certain extent, there are still some problems and shortcomings. First, the existing passivation layer materials may not be able to effectively suppress the interface charge recombination, resulting in low efficiency of the battery. Second, the existing passivation layer materials may have a negative impact on the stability of the perovskite and affect the long-term performance of the battery. In addition, the existing passivation layer preparation method is complicated and costly, which is not conducive to large-scale production. Summary of the invention
[0005] In order to overcome the problem that the existing passivation layer materials in the prior art may not be able to effectively suppress the interface charge recombination, which has a negative impact on the stability of the perovskite, thereby leading to the problems of low efficiency and poor stability of the battery, the present invention provides a new passivation layer for the surface of the perovskite absorption layer and a battery thereof. By using the compound of formula A of the present invention to prepare the passivation layer, the radius of the perovskite grain can be increased, the problem of charge recombination at the interface of the perovskite can be effectively solved, the carrier mobility and defect state density of the battery can be improved, and the extraction ability of photogenerated electrons can be enhanced, thereby improving the efficiency and stability of the battery.
[0006] Specifically, the first aspect of the present invention provides a passivation layer for use on the surface of a perovskite absorption layer, wherein the material of the passivation layer comprises a compound of formula A:
[0007]
[0008] Wherein, L is selected from N + A five-membered or six-membered heteroaryl group formed with a carbon atom, or N + (R1)(R2)(R3), wherein R1, R2, and R3 are each independently selected from substituted or unsubstituted C1-10 alkyl;
[0009] The value of n is 2-20.
[0010] In one or more embodiments, n is 3-10.
[0011] In one or more scenarios, N + The five-membered or six-membered heteroaryl group formed with carbon atoms is a pyridyl group.
[0012] In one or more embodiments, R1, R2, and R3 are each independently selected from substituted or unsubstituted C1-4 alkyl.
[0013] In one or more embodiments, the substituted C1-4 alkyl group is a halogenated C1-4 alkyl group.
[0014] In one or more embodiments, the halogenated C1-4 alkyl group is a C1-4 alkyl group substituted with 1 to 10 or 1 to 5 halogens.
[0015] In one or more embodiments, the compound of formula A is selected from compounds of formula (1) to formula (4):
[0016]
[0017] The second aspect of the present invention provides a method for preparing a passivation layer as described in any embodiment of the present invention or improving the crystallinity of perovskite and the ability to extract photogenerated electrons, the method comprising the following steps:
[0018] The passivation layer solution is coated on the surface of the perovskite absorption layer, and after annealing, the passivation layer is obtained; wherein the passivation layer solution contains a solvent and the compound of formula A as described in any embodiment of the present invention.
[0019] In one or more embodiments, the coating method includes one or more processes of spin coating, blade coating, evaporation, printing, spray coating, spray pyrolysis, and slit coating.
[0020] In one or more embodiments, in the passivation layer solution, the mass concentration of the compound of formula A is 0.1 mg / ml-5 mg / ml.
[0021] In one or more embodiments, the solvent is selected from one or more of isopropanol, ethanol and methanol.
[0022] In one or more embodiments, the annealing temperature is 50-300° C., and the annealing time is 5-30 min.
[0023] A third aspect of the present invention provides a perovskite solar cell, which comprises a stacked conductive glass layer, a hole transport layer, a perovskite light absorbing layer, a passivation layer, an electron transport layer and an electrode, wherein the material of the passivation layer is selected from the compound of formula A as described in any embodiment of the present invention, and optionally, a hole blocking layer is further provided between the electron transport layer and the electrode.
[0024] In one or more embodiments, the material of the electron transport layer is selected from at least one of [6,6]-phenyl-C61-butyric acid methyl ester, C60 and tin oxide.
[0025] In one or more embodiments, the material of the perovskite light absorbing layer comprises a first perovskite material and a second perovskite material; wherein the first perovskite material is selected from at least one of lead halide salts and tin halide salts, and the second perovskite material is selected from at least one of formamidine halide salts, methylamine halide salts and cesium halide salts.
[0026] In one or more embodiments, the hole blocking layer is made of a material selected from 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline or zirconium acetylacetonate.
[0027] In one or more embodiments, the material of the electrode is selected from at least one of silver, copper, conductive oxide and carbon electrode.
[0028] A fourth aspect of the present invention provides the use of a compound of formula A as described in any embodiment herein for passivating surface and grain boundary defects of a perovskite film and / or improving the interface contact between an electron transport layer and perovskite to enhance the ability to extract photogenerated electrons.
[0029] A fifth aspect of the present invention provides the use of a compound of formula A as described in any embodiment herein in the preparation of a passivation layer or a perovskite solar cell.
[0030] Beneficial effects of the present invention:
[0031] ① The present invention uses a zwitterionic polymer material formula A compound as a passivation layer material for the perovskite absorption layer, which can effectively passivate the perovskite surface and inhibit the charge recombination at the interface between the perovskite and the electron transport layer, thereby improving the efficiency of the perovskite photovoltaic device. Compared with the prior art, the perovskite passivation material of the present invention can more effectively solve the problem of interfacial charge recombination of the perovskite absorption layer and improve the photoelectric conversion efficiency of the battery.
[0032] ② The zwitterionic polymer material formula A compound of the present invention has little effect on the stability of perovskite, which is conducive to maintaining the long-term performance of the battery. Compared with the prior art, the passivation layer material or passivation layer material of the present invention can avoid negative impact on the stability of perovskite and ensure the long-term performance of the battery.
[0033] ③ Compared with the prior art, the passivation layer preparation method of the present invention is simpler, has lower cost, is more suitable for large-scale production, and has higher practical value. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 It is a schematic diagram of the device structure of the perovskite solar cell of the present invention.
[0035] Figure 2 This is the SEM image of the passivation layer prepared in Example 1.
[0036] Figure 3 This is the SEM image of the passivation layer prepared in Example 2.
[0037] Figure 4 This is the SEM image of the passivation layer prepared in Example 3.
[0038] Figure 5 This is the SEM image of the passivation layer prepared in Example 6.
[0039] Figure 6 This is the SEM image of the passivation layer prepared in Comparative Example 1. DETAILED DESCRIPTION
[0040] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.
[0041] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.
[0042] Herein, “comprising”, “including”, “containing” and similar terms encompass the meanings of “consisting essentially of” and “consisting of”. For example, when “A comprises B and C” is disclosed herein, “A consists essentially of B and C” and “A consists of B and C” should be deemed to be disclosed herein.
[0043] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are only for brevity and convenience. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values within the range (including integers and fractions).
[0044] In this document, unless otherwise specified, percentage refers to mass percentage and ratio refers to mass ratio.
[0045] Herein, when describing embodiments or examples, it should be understood that they are not used to limit the present invention to these embodiments or examples. On the contrary, all substitutes, improvements and equivalents of the methods and materials described in the present invention can be included in the scope limited by the claims.
[0046] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.
[0047] The main purpose of the present invention is to provide an application of a zwitterionic passivator formula A compound in passivating perovskite materials, especially in the perovskite absorption layer of a passivating perovskite solar cell. The present invention introduces a zwitterionic passivator formula A compound as a material to prepare a passivation layer on the surface of the perovskite, thereby inducing recrystallization of small perovskite grains, reducing grain boundaries, and passivating the surface and grain boundary defects of the perovskite film. At the same time, the interface contact between the electron transport layer and the perovskite is improved, and the ability to extract photogenerated electrons is enhanced.
[0048] In some embodiments, such as Figure 1 As shown, the perovskite solar cell includes a conductive glass layer, a hole transport layer, a perovskite light absorption layer, a passivation layer, an electron transport layer and an electrode from bottom to top.
[0049] Therefore, the present invention provides a passivation layer for use on the surface of a perovskite absorber layer, comprising a compound of formula A:
[0050]
[0051] Wherein, L is selected from N + A five-membered or six-membered heteroaryl group formed with a carbon atom, or N + (R1)(R2)(R3), wherein R1, R2, and R3 are each independently selected from substituted or unsubstituted C1-10 alkyl groups; and the value of n is 2-20.
[0052] In some embodiments, n is 3-10, such as 4-5 or 6-10.
[0053] In some embodiments, R1, R2, and R3 are each independently selected from substituted or unsubstituted C1-4 alkyl.
[0054] In some embodiments, the substituted C1-4 alkyl is a halogenated C1-4 alkyl.
[0055] In some embodiments, the halo-substituted C1-4 alkyl group is a C1-4 alkyl group substituted with 1-10 or 1-5 halogens.
[0056] In some specific embodiments, the compound of formula A is selected from one or more compounds of formula (1) to formula (4):
[0057]
[0058] In some embodiments, the compound of formula A is selected from a compound of formula I, a compound of formula II, a compound of formula III, or a compound of formula IV.
[0059] The passivation layer of the present invention can be prepared by a solution process.
[0060] In some embodiments, the present invention provides a method for preparing a passivation layer, which comprises mixing a compound of formula A and a solvent to obtain a passivation layer solution; coating the passivation layer solution on the surface of a perovskite absorption layer, and annealing to obtain a passivation layer.
[0061] In some embodiments, the compound of formula A and a solvent may be mixed and stirred at room temperature to obtain a passivation layer solution. The type of solvent is not particularly limited and may be selected from organic solvents conventionally used in the art, such as one or more selected from isopropanol, ethanol and methanol.
[0062] In some embodiments, the mass concentration of the compound of formula A in the passivation layer solution is 0.1 mg / ml-5 mg / ml.
[0063] In some embodiments, the compound of formula A is selected from one or more of the compounds of formula (1) to formula (4).
[0064] In the present invention, in some embodiments, the passivation layer solution is coated on the surface of the perovskite absorption layer by a spin coating process. The coating thickness of the passivation layer solution on the surface of the perovskite absorption layer can be adjusted according to the target thickness of the passivation layer. In the spin coating process, the spin coating rate can be 4500-5000 rpm, and the spin coating time can be 30-40 s.
[0065] In the present invention, the coating method may also include one or more processes of slit coating, blade coating, spray coating, screen printing, and inkjet printing. The parameters of these processes may be adjusted according to the target thickness of the passivation layer.
[0066] After coating, annealing is performed. The purpose of annealing is to remove the solvent. The annealing temperature is 50-300° C. The exemplary annealing time may be 5-30 minutes.
[0067] In some embodiments, the thickness of the passivation layer is 1-10 nm.
[0068] The present invention also provides a perovskite solar cell, which comprises a perovskite absorption layer and a passivation layer as described herein disposed on the surface of the perovskite absorption layer.
[0069] The present invention also provides a method for preparing a perovskite solar cell, which includes the steps of sequentially arranging a hole transport layer, a perovskite light absorbing layer, a passivation layer, an electron transport layer and an electrode on a conductive transparent glass layer, wherein the passivation layer may be arranged using the steps for preparing the passivation layer described herein. In some embodiments, the step of arranging a hole blocking layer between the electron transport layer and the electrode is also included.
[0070] Therefore, the perovskite solar cell of the present invention may include a stacked conductive glass layer, a hole transport layer, a perovskite light absorbing layer, a passivation layer described herein, an electron transport layer and an electrode, and optionally, a hole blocking layer is further provided between the electron transport layer and the electrode.
[0071] The conductive material suitable for the conductive glass layer of the present invention includes, but is not limited to, one or more of FTO, ITO, and IZO. The preparation of the conductive glass layer is not particularly limited, and the conventional method for preparing the conductive glass layer in the art can be used, such as a magnetron sputtering process. The process parameters can be adjusted according to the target thickness of the conductive layer.
[0072] Materials suitable for the hole transport layer of the present invention include, but are not limited to, NiOx, SAM (self-assembled monomolecular film materials), etc. The types of SAM materials are not particularly limited, including but not limited to carbazole phosphonic acid, etc. The preparation of the hole transport layer is not particularly limited, and the conventional method for preparing the hole transport layer in the art can be used, such as spin coating, blade coating or slit coating. The process parameters can be adjusted according to the target thickness of the hole transport layer. In some embodiments, the thickness of the hole transport layer is 2-5nm.
[0073] The active material of the perovskite active layer suitable for the present invention comprises a first perovskite material and a second perovskite material; wherein the first perovskite material is selected from at least one of a lead halide salt and a tin halide salt, and the second perovskite material is selected from at least one of a formamidine halide salt, a methylamine halide salt and a cesium halide salt. In some embodiments, the materials of the perovskite absorption layer are lead iodide and iodomethylamine. The preparation of the perovskite active layer is not particularly limited, and the conventional method for preparing the perovskite active layer in the art can be used, including but not limited to one or more of spin coating, blade coating, evaporation, printing, spraying, spray pyrolysis, and slit coating. The process parameters can be adjusted according to the target thickness of the perovskite absorption layer. In some embodiments, the thickness of the perovskite absorption layer is 450nm-550nm.
[0074] Materials suitable for the electron transport layer of the present invention include, but are not limited to, one or more of [6,6]-phenyl-C61-butyric acid methyl ester, C60 and tin oxide. The preparation of the electron transport layer is not particularly limited, and the conventional method for preparing the electron transport layer in the art can be used, including but not limited to one or more of spin coating, spray coating, spray pyrolysis, slit coating, and atomic layer deposition. The process parameters can be adjusted according to the target thickness of the electron transport layer. In some embodiments, the thickness of the electron transport layer is 10nm-100nm, such as 20-40nm.
[0075] Materials suitable for the hole blocking layer of the present invention include, but are not limited to, 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline and zirconium acetylacetonate. The preparation of the hole blocking layer is not particularly limited, and the conventional method for preparing the hole blocking layer in the art can be used, including but not limited to one or more of spin coating, spray coating, spray pyrolysis, slit coating, and atomic layer deposition. The process parameters can be adjusted according to the target thickness of the hole blocking layer. In some embodiments, the thickness of the hole blocking layer is 1nm-10nm, such as 5-8nm.
[0076] The material suitable for the electrode of the present invention can be selected from one or more of silver, copper, conductive oxide and carbon electrode. In some embodiments, the thickness of the electrode is 90nm-400nm, such as 80-150nm.
[0077] The present invention will be described below in the form of specific examples. It should be understood that these examples are merely illustrative and are not intended to limit the scope of the present invention. The methods, reagents and materials used in the examples are, unless otherwise stated, conventional methods, reagents and materials in the art. The raw material compounds in the examples can all be purchased through commercial routes.
[0078] Example 1
[0079] 1. Ultrasonic clean the TCO conductive glass with deionized water, acetone and isopropanol for 15 minutes respectively, and finally put it into a drying oven at 75°C for use; put the dried TCO glass substrate into a UV ozone machine for 5 minutes to remove organic impurities on its surface and optimize its surface wettability;
[0080] 2. Dissolve 1 mg 2PACz in 2 mL chlorobenzene and stir at room temperature until completely dissolved to obtain an organic hole transport material solution;
[0081] 3. Take 30uL of organic hole transport material solution, drop it on the treated TCO glass, spin coat it at 5000rpm for 30s, and heat and anneal it at 100℃ on a hot stage for 10min to form a hole transport layer;
[0082] 4. Dissolve 722.08 mg of lead iodide and 238.50 mg of iodomethylamine solid in 1 mL of N,N-dimethylformamide (DMF), stir at room temperature until completely dissolved, and obtain a perovskite precursor solution; in a nitrogen glove box, take 30 μL of the perovskite precursor solution and drop it on the ITO conductive glass that forms the hole transport layer, first spin-coat it at 1000 rpm for 10 seconds, then spin-coat it at 5000 rpm for 30 seconds, and quickly drop 125 μL of chlorobenzene at 25 seconds in this process, and then put the TCO glass on a hot stage and heat it at 100°C for 40 minutes to form a perovskite light-absorbing layer of 500 nm;
[0083] 6. Dissolve 2.0 mg of the compound SAS of formula I (wherein n is 4) in 1 mL of isopropanol and stir at room temperature to obtain a passivation layer solution;
[0084] 7. Take 75uL of the passivation layer solution and drop it on the top of the perovskite layer, spin-coat at 5000rpm for 35s, and anneal at 100℃ for 10min to form a passivation layer;
[0085] 8. Dissolve 20 mg of methanefullerene phenyl-C61-butyric acid methyl ester (PCBM) in 1 mL of chlorobenzene and stir at room temperature to obtain [6,6]-phenyl-C61-butyric acid methyl ester solution;
[0086] 9. Take 30uL of [6,6]-phenyl-C61-butyric acid methyl ester solution and drop it on the ITO conductive glass with the passivation layer perovskite, and spin coat at 3000rpm for 60s to form an electron transport layer;
[0087] 10. Transfer the TCO conductive glass with electron transport layer, passivation layer, perovskite layer and hole transport layer to the vacuum coating instrument and wait until the vacuum degree reaches 3*10 -4 A silver electrode was evaporated at 100 nm in thickness to obtain an electrode layer.
[0088] Example 2
[0089] The only difference between Example 2 and Example 1 is that the compound of formula I is replaced by the compound of formula II Et SAS (wherein n is 5).
[0090] Example 3
[0091] The only difference between Example 3 and Example 1 is that the compound of formula I is replaced by the compound of formula III Pr SAS (wherein n is 4).
[0092] Example 4
[0093] The only difference between Example 4 and Example 1 is that the compound of formula I is replaced by the compound of formula IV Py SAS (wherein n is 4).
[0094] Example 5
[0095] The only difference between Example 5 and Example 1 is that n is 10 in the compound of formula I.
[0096] Comparative Example 1
[0097] The only difference between Example 4 and Example 1 is that a perovskite cell passivation layer is not prepared.
[0098] Test Example 1
[0099] Photoelectric tests were performed on the perovskite solar cells prepared in Examples 1-4 and Comparative Examples 1-2. The test temperature was 25±1°C. The current density-voltage curves (JV curves) of the devices were obtained by using a source meter (Keithley 2400) under AM1.5G (100 mW / cm 2 ) obtained under illumination, the cell area is 0.04907cm 2 ,The light intensity was calibrated by a standard silicon cell before testing, and the scanning rate was 10mV / s.
[0100] The open circuit voltage is the terminal voltage of the battery in the open circuit state. The short circuit current is the current density that the perovskite solar cell can generate under short circuit conditions. The fill factor is the ratio of the maximum power of the solar cell to the product of the open circuit voltage and the short circuit current. The photoelectric conversion efficiency can be calculated by measuring the current density-voltage curve (JV curves) of the solar cell.
[0101] The results are shown in Table 1 below.
[0102] Table 1. Photoelectric test results
[0103] <![CDATA[Jsc(mA / cm 2 )]]> Voc(V) FF(%) Eff(%) Example 1 24.59 1.15 82.9 23.46 Example 2 24.51 1.16 82.6 23.74 Example 3 24.48 1.17 83.3 23.56 Example 4 24.39 1.15 83.1 23.72 Example 5 24.23 1.13 81.82 22.29 Comparative Example 1 24.10 1.10 79.4 21.07
[0104] As shown in Table 1, compared with Comparative Example 1, Examples 1-5 use the compound of formula A of the present invention to prepare the passivation layer, which can improve the photoelectric conversion efficiency and fill factor of the device. Among them, Example 5 has a certain passivation effect, but the improvement effect is not as good as that of Examples 1-4. This is because when the polymerization degree is too high, the solubility decreases, and the film-forming effect of the passivation layer is relatively not as good as that of Examples 1-4, but better than that of the comparative example.
[0105] Test Example 2
[0106] The passivation layers prepared in Examples 1-4 and Comparative Example 1 were observed by electron microscope scanning and images were obtained. Figure 2 This is the SEM image of the passivation layer prepared in Example 1. Figure 3 This is the SEM image of the passivation layer prepared in Example 2. Figure 4 This is the SEM image of the passivation layer prepared in Example 3. Figure 5 This is the SEM image of the passivation layer prepared in Example 6. Figure 6 This is the SEM image of the passivation layer prepared in Comparative Example 1.
[0107] Table 1 below shows the maximum grain radius data of the passivation layers of Examples 1-4 and Comparative Example 1.
[0108] Table 1. Maximum grain radius data
[0109] Serial number Maximum grain radius Comparative Example 1 543nm Example 1 1.06μm Example 2 1.76μm Example 3 1.44μm Example 4 1.45μm
[0110] It can be seen from the SEM images of Examples 1-4 and Comparative Example 1 and Table 1 that, relative to Comparative Example 1, the passivation layers of Examples 1-4 significantly increase the perovskite grain radius and reduce the grain boundaries in the film.
[0111] Test Example 3
[0112] The carrier mobility and defect state density of the perovskite cells prepared in Examples 1-4 and Comparative Example 1 were measured.
[0113] Carrier mobility: The pure electronic device model used for SCLC (space charge limited current) mobility test is ITO / TiO2 / PVK / SAS / PCBM / Ag. The mobility is determined by the SCLC model. The calculation formula of the model is: J = (8 / 9) με0ε r (V 2 / L 3 );
[0114] where ε0 is the permittivity of free space (8.85×10 -12 F m -1 ), ε ris the dielectric constant of PCBM (assumed to be 3), μ is the electron mobility, V is the voltage, and L is the film thickness (250 nm). All current-voltage (IV) characteristics of the field effect transistor (FET) were measured using a Keithley 4200 semiconductor characterization system connected to a probe station in a N2-filled chamber.
[0115] Defect state density test:
[0116] Trap defect state density (N t ) by the trap filling limit voltage (V TFL )Decide:
[0117]
[0118] Where L is the thickness of the perovskite film, V TFL is the starting voltage of the trap filling limit region, ε r is the relative dielectric constant of the perovskite film, ε0 is the vacuum permittivity, and q is the electron charge. TFL It is obtained from SCLC test, and the other parameters are constants.
[0119] The measurement results are shown in Table 2.
[0120] Table 2. Carrier mobility and defect state density data
[0121]
[0122] As shown in Table 2 above, relative to Comparative Example 1, the mobility of Examples 1-4 increased and the defect state density decreased, both indicating that the ability to extract photogenerated carriers was enhanced and the generation of non-radiative recombination was reduced.
Claims
1. A passivation layer for use on the surface of a perovskite absorption layer, characterized in that: The material of the passivation layer includes a compound of formula A: Wherein, L is selected from N + A five-membered or six-membered heteroaryl group or N + (R1)(R2)(R3), wherein R1, R2, and R3 are each independently selected from substituted or unsubstituted C1-10 alkyl; The value of n is 2-20.
2. The passivation layer according to claim 1, characterized in that The value of n is 3-10; and / or R1, R2, and R3 are each independently selected from substituted or unsubstituted C1-4 alkyl.
3. The passivation layer according to claim 2, characterized in that The substituted C1-4 alkyl group is a halogenated C1-4 alkyl group; The halogenated C1-4 alkyl group is a C1-4 alkyl group substituted with 1 to 10 or 1 to 5 halogens.
4. The passivation layer according to claim 1, characterized in that The compound of formula A is selected from the compounds of formula (1) to formula (4):
5. A method for preparing a passivation layer as claimed in any one of claims 1 to 4 or improving the crystallinity of perovskite and the ability to extract photogenerated electrons, characterized in that: The method comprises the following steps: The passivation layer solution is coated on the surface of the perovskite absorption layer, and after annealing, the passivation layer is obtained; wherein the passivation layer solution contains a solvent and the compound of formula A as described in any one of claims 1 to 4.
6. The method according to claim 5, characterized in that: The coating method includes one or more processes of spin coating, blade coating, evaporation, printing, spray coating, spray pyrolysis, and slit coating; In the passivation layer solution, the mass concentration of the compound of formula A is 0.1 mg / ml-5 mg / ml; The solvent is selected from one or more of isopropanol, ethanol and methanol.
7. The method according to claim 5, characterized in that The annealing temperature is 50-300°C, and the annealing time is 5-30 minutes.
8. A perovskite solar cell, characterized in that: The perovskite solar cell comprises a stacked conductive glass layer, a hole transport layer, a perovskite light absorbing layer, a passivation layer, an electron transport layer and an electrode, wherein the material of the passivation layer is selected from the compound of formula A described in any one of claims 1 to 4, and optionally, a hole blocking layer is further provided between the electron transport layer and the electrode.
9. The perovskite solar cell according to claim 8, characterized in that: The material of the electron transport layer is selected from at least one of [6,6]-phenyl-C61-butyric acid methyl ester, C60 and tin oxide; The material of the perovskite light-absorbing layer comprises a first perovskite material and a second perovskite material; wherein the first perovskite material is selected from at least one of a lead halide salt and a tin halide salt, and the second perovskite material is selected from at least one of a formamidine halide salt, a methylamine halide salt and a cesium halide salt; The material of the hole blocking layer is selected from 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline or zirconium acetylacetonate; The material of the electrode is selected from at least one of silver, copper, conductive oxide and carbon electrode. 10.Select from the following applications: Use of the compound of formula A as described in any one of claims 1 to 4 in passivating the surface and grain boundary defects of a perovskite film and / or improving the interface contact between an electron transport layer and perovskite to enhance the ability to extract photogenerated electrons; Use of the compound of formula A as claimed in any one of claims 1 to 4 in the preparation of a passivation layer or a perovskite solar cell.
Citation Information
Patent Citations
Perovskite passivation material, passivation unit and perovskite battery
CN119277948A
Ammonium and sulfonium sulfonate zwitterions and polymers derived therefrom
US20230331918A1